ANALYSIS OF EFL LEARNERS’ DIFFICULTIES IN OFFLINE CLASSROOM LEARNING - L, Syahrir; H, Zulkifli; Andi Sadapotto; Sitti Aisa; Sam Hermansyah (JURNAL ILMIAH EDUNOMIKA, 2025)
This research investigates the difficulties faced by second-semester students of the English Education Program at Universitas Muhammadiyah Sidenreng Rappang in learning English as a Foreign Language (EFL) in offline classroom settings. The research problem focuses on identifying linguistic, psychological, and contextual factors that hinder effective learning. The main objective is to analyze these challenges and provide insights for improving teaching and learning practices. Employing a qualitative descriptive method, data were collected through semi-structured interviews, classroom observations, and documentation from 15 purposively selected students. Data analysis followed Miles and Huberman’s (1994) framework data reduction, data display, and conclusion drawing supported by NVivo software for thematic coding. Findings reveal that linguistic difficulties, particularly in listening comprehension, grammar mastery, pronunciation, and vocabulary, are the most dominant obstacles. Psychological barriers such as speaking anxiety, fear of mistakes, and low self-confidence further impede participation. Contextual issues, including noisy classrooms, ineffective teaching methods, and limited speaking practice, exacerbate the problem. Despite these challenges, students suggested interactive teaching strategies, such as games, storytelling, audiovisual aids, and real-life examples, to enhance engagement and comprehension. The research concludes that addressing both cognitive and affective needs through student-centered and communicative approaches, alongside improving classroom management and teaching materials, is essential for fostering a more effective EFL learning environment.